Participation of rural women in goat rearing in a selected area of Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
The main purpose of this study was to assess participation of rural women in goat rearing. Pakulla union under Sonatola upazila of Bogra district in Bangladesh was the locale of the study. All the rural goat rearing farm family women heads of Pakulla union constituted the population of the study. Data were collected from a sample of 100 women heads selected randomly during15 December 2008 to 14 January, 2009. The extent of participation of rural women in fifteen items of goat rearing activities was measured through a five-point rating scale. Ten selected characteristics of women were independent variables. Coefficient of correlation ‘r' was computed to test relationship between the dependent and independent variables. Findings revealed that participation of women in goat rearing ranged from 20 to 48 against expected value 0 to 60 with a mean of 35.87 and standard deviation of 8.64. Data also showed that largest portion (63 percent) of the respondents fell into medium participation categories while 28 percent and 9 percent fell into low and high participation categories respectively. Data revealed that participation of rural women in the item ‘excreta cleaning of goat' had the highest participation index (PI= 327) and ranked 1st , ‘looking after the kids' had the second highest participation with PI of 315 and participation in 'caring during pregnancy period' was in 3rd position with PI of 307 among 15 items. On the other hand the lowest participation was observed in ‘arrangement of vaccination' (PI= 21) and in ‘castration in time' with PI of 46 among these 15 items. Correlation analyses indicate that knowledge about goat rearing and extension media contacts were found to have positively significant relationship with participation in goat rearing. On the other hand education, farm size, annual income had negative significant correlation with participation in goat rearing while respondents' age, marital status, family size, credit receipt and grazing land availability had no significant relation with participation in goat rearing. Regarding problem confrontation in goat rearing, data indicated that among the 10 major problems ‘lack of proper training about goat rearing' ranked first with 251 problem index (PI). Lack of available grazing land came next in rank (rank 2, PI 242). High mortality rate of kids was the next problem (rank 3, PI 216). Keywords: Participation; Rural women; Goat rearing DOI: 10.3329/jbau.v7i2.4747 J. Bangladesh Agril. Univ. 7(2): 361-366, 2009